Delocalizing Communities: Changing Forms of Community Engagement in Natural Resources Governance. (November 2016) - Ojha, Hemant R.; Ford, Rebecca; Keenan, Rodney J.; Race, Digby; Carias Vega, Dora; Baral, Himlal; Sapkota, Prativa
Highlights: Diverse interests in natural resources delocalize communities beyond "local" level. Locally-framed, rule-focused and place-based communities are less common. Delocalization involves the exchange of and struggle for various capitals. We suggest recognizing such delocalizing communities in resource governance. Summary: Across both the developing and developed worlds, community engagement has become a key strategy for natural resource management. However, a growing number of studies report that community-based approaches are experiencing formidable challenges, with limited outcomes in terms of livelihoods, decentralization and sustainability. Yet, policies continue to focus attention unduly on "community participation", ignoring the ways in which the "community" is itself embedded in a wider social system. Recent studies have shown that local communities are more complex than previously assumed, with local community actions being heavily shaped by wider social and environmental contexts. Yet, scholarly research tends to focus on reporting such cross-scalar dynamics, with little explanation of how and why they occur. This paper advances a framework to understand how local communities interact with the wider world, through what we term "delocalization of communities" in natural resource management. Using Bourdieu's theory of social field, we present an approach to analyze various trajectories of delocalization involving the exchange of, and struggle for, a variety of resources valued in specific fields of natural resource governance. We extend the work of several researchers who have been critical of the conventional view of the community, and argue that a new model of delocalized "community" needs to be envisaged, one that emphasizes the interactions among actors within and between spatial scales and levels of political organization. While such a cross-scalar view is not novel, we deepen social field approach to assess how cross-scalar processes unfold in the course of "delocalization" of communities in the context of rapid social and environmental change. We draw on evidence from five different case studies from three continents that demonstrate specific aspects of the delocalization phenomenon. The cases selected are from Australia, Indonesia, Mexico, Nepal, and Papua New Guinea. We demonstrate through these cases that increasingly diverse interests in natural resources such as forests have served to delocalize communities beyond "local" domains. We conclude that local community is not a localized entity, and there are multiple cross-scale networks which need to be recognized, as these have profound implications in community-based natural resource management. In such situations, open and exploratory approaches - moving away from blueprint interventions - are required to facilitate context-specific fields and spheres of local democracy, nurturing diverse, flexible, and networked models of community participation, along with the recognition of political and economic influence coming from the wider domain.